A New Look at Debt Rescheduling Indicators and Models - Morgan, John B. (Journal of International Business Studies, 1986)
This paper presents logit and discriminant models of debt rescheduling. The models incorporated new short-term debt data and variables representing economic shocks. The 30-country database covered the period from 1975 to 1982 and contained the largest number of debt rescheduling observations of any previous database. Because of the new indicators and more recent data, the models captured the effects of the changes that have occurred in the world economy since the oil price shocks and the period of rapid debt accumulation by the developing countries. Compared to the earlier research models, the models have proven to be efficient in forecasting debt reschedulings.